The values of character education in the pakeliran art “Lord Shiva Saves the Universe” - Komang Sekar Marhaeni; Ni Ketut Dewi Yulianti; I Ketut Garwa (Journal of Aesthetics, Creativity and Art Management, 2022)
The purpose of this paper is to analyze the values of character education in the traditional art of “Lord Shiva Saves the Universe” and the moral messages contained in it, which are beneficial not only for humanists and artists, but also for activists in the field of character education. The method used is a qualitative by analyzing the performance of "Lord Shiva Saves the Universe" which is an English language performance art whose play is adapted from the Srimad Bhagavatam skanda 8 in chapter 7 with the title Lord Shiva Saves the Universe by Drinking Poison. The character values contained in the traditional art of "Lord Shiva Saves the Universe" are: 1) religious, 2) tolerance, 3) discipline, 4) hard work, 5) creative, and 6) responsibility. The moral message contained in it reminds everyone to be careful in believing someone's appearance because a charming appearance can be a trap to deceive someone. This is very important to study, considering that there are currently many declines in the character of the nation's children and also national problems, such as reduced ethical values in the life of the nation and state.